The Effect of E-Learning Approach on Studentsa Achievement in Fraction Math Course Level 5 at Yemens Public Primary School (Global Journal of Computer Science and Technology, 2014)
E-learning (EL) is widely used in school and other organizations all over the world, because of difficulties in math skills (Remembering , understanding , application). There have not been any major surveys in the Yemen Public Primary School (YPPS) in that regard. This is the driving question behind this research: What is the effectiveness and usefulness of using e-learning approach in teaching the fraction math course for students of level 5 in the republic of Yemen on (Remembering , understanding , application) skills ? In this study, an experimental group of (30) students studying a course using e-learning approach. The control group (30) students they studying a course traditional learning, experimental design approach were used. The students2019; achievement was examined between two groups. The research results proved that there is a significant increase in gain in achievement, The EL has achieved efficiency greater than traditional learning in (Remembering, understanding, application) skills.
Keywords: control group; e-learning; experimental group; pre-test; post-test; students2019; achievement; t-test